2015
DOI: 10.4103/0974-8237.161589
|View full text |Cite
|
Sign up to set email alerts
|

Pain management following spinal surgeries: An appraisal of the available options

Abstract: Spinal procedures are generally associated with intense pain in the postoperative period, especially for the initial few days. Adequate pain management in this period has been seen to correlate well with improved functional outcome, early ambulation, early discharge, and preventing the development of chronic pain. A diverse array of pharmacological options exists for the effective amelioration of post spinal surgery pain. Each of these drugs possesses inherent advantages and disadvantages which restricts their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
154
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(164 citation statements)
references
References 60 publications
2
154
0
8
Order By: Relevance
“…7 In comparing 179 surgical procedures over a 6-year period, one study reported that single and multilevel spinal fusions were among the top most painful surgeries performed. 19 It is therefore critical that adequate pain relief be achieved in order to facilitate early mobilization, which has been shown to decrease the hospital length of stay and improve back functionality in patients having undergone spine surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In comparing 179 surgical procedures over a 6-year period, one study reported that single and multilevel spinal fusions were among the top most painful surgeries performed. 19 It is therefore critical that adequate pain relief be achieved in order to facilitate early mobilization, which has been shown to decrease the hospital length of stay and improve back functionality in patients having undergone spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…4 Current regimens involve the use of opioid, nonopioid analgesics, and/or local anesthetics. [5][6][7] Local infiltration of anesthetics in the surgical site during wound closure is commonly performed with lumbar spine surgery. 8,9 These agents are traditionally used to provide postoperative analgesia, but the effects are limited by dosing restrictions due to potential systemic side effects from peak plasma concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Th e pain after discectomy is severe and typically lasts for three days 12 . It is directly proportional to the number of levels involved and is similar in surgeries of cervical, thoracic and lumbar region [13][14][15][16] . Postoperative pain is transitory and gradually improves making it more amenable to medical therapy in comparison to chronic pain 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic use of these medications leads to an altered perception of pain and reduced response to common medications [11]. Therefore, a protocol aimed at reducing narcotic consumption and focusing on the variety of pain mechanisms is necessary to adequately manage this patient population's postoperative pain [6,25].…”
Section: Introductionmentioning
confidence: 99%
“…Infiltration of the surrounding soft tissue with lidocaine and epinephrine prior to skin incision, as well as the use of 30-40 mLs of ropivacaine 0.5% at skin closure, reduced postoperative pain and opioid consumption [33,34]. Additionally, the use of postoperative epidural analgesia has been associated with significant improvements region involved (cervical, thoracic, or lumbar) [11]. Several of the biochemical pathways that contribute to postoperative pain originate with the surgical incision.…”
Section: Introductionmentioning
confidence: 99%